SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN KELAYAKAN ARTIKEL JURNAL ILMIAH DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) (Studi Kasus : Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti) - Shidqon, Moh; Gunadi, Goldie (Infotech: Journal of Technology Information, 2023)
Change the paradigm of scientific periodicals into electronic printed must follow its development by the author or publisher in Indonesian. The changes led to the accreditation process supported by technology article that qualified. In addition to the feasibility assessment, the article selection process was still using a manual system is not computerized. Issuing the Faculty of Economics and Business (LPFEB) Trisakti University requires a database application that can accommodate the editing process LPFEB article contained in Trisakti University. Management of scientific journals in the process of determining the feasibility of the journal to be published this takes quite a relatively long, making it difficult to assess the reviewer section. From the problems in the wake of website database based on PHP and MySQL using the SAW (Simple Additive Weighting) is capable of supporting the process of the ongoing feasibility assessment. With the construction of this database can facilitate reviewer in determining the feasibility of a scientific journal, so that the application site can be more efficient editing process.